Pengaruh Pemberian Cookies Bunite terhadap Kadar Gula Darah Sewaktu pada Penderita DM Tipe 2 - Muzakar, Muzakar; Dewi, Arifah Rahma; Listrianah, Listrianah (Poltekkes Kemenkes Tanjung Karang, 2021)
The prevalence of DM in Indonesia in 2018 was 2.0% and in South Sumatra was 20,7%. Non-pharmacological management of DM is by giving